Aphasic subjects rehabilitation: a social-interactionist perspective - Cecília Farah da Silva; Leticia Guedes Cintra (O Mundo da Saúde)
Aphasia is among the different pathologies that affect language and may cause alterations in social, professional, emotional and personal life of individuals affected by it. It is necessary to investigate the impact generated by language privation in the life of these individuals, something which will allow the therapist to propose rehabilitation strategies, so that these subjects regain the ability for meaning making and to contextualize language, participating on different interaction situations. The present work aimed at approaching the contributions of the social-interactionist theory of language acquisition in the therapy of aphasic subjects, looking for the implications of language alterations in the interactional process and the social and emotional aspects of these individuals. For the accomplishment of the study, we did on-line searches in manuals, scientific articles and reading.